Re-Mapping Opportunity : Making Best Use of the Economic Potential of Russia's Regions - World Bank (World Bank, Washington, DC, 2018)
In order to understand a country as large and diverse as Russia, it is extremely important to consider spatial patterns of economic development. As Russia looks for new drivers of economic growth, it is important to understand the structural conditions that have defined economic development in Russia’s regions. This report uses the Economic Potential Index (EPI) methodology to identify the conditions that drive regional development. Economic potential is the level of productivity that is possible for a region to achieve given its structural endowments, which are characteristics that are hard to alter in the short run. The methodology used in this report combines quantitative analysis of drivers of productivity across regions with in-depth case studies that focus on the role of regional governments and institutions in converting endowments into economic outcomes. This methodology generates insights that are relevant for both national and regional governments. The first chapter of this report provides an overview of regional development in Russia over the last 25 years and identifies “Russia-specific” national structural conditions that may affect regional development. The second chapter discusses the results of an assessment of economic potential at the regional level and the factors that shape it in Russia. The third chapter focuses on the role of national and regional governance, policy, and institutions in promoting economic development of the regions. The final chapter proposes policy priorities for both regional and national authorities.